An appraisal on maritime boundary delimitation by Bangladesh and Norway - Islam, Md. Zahidul; Islam, Md. Asraful (Asian and African Research Centre, 2022)
This study analyses the maritime claims and maritime boundaries of Bangladesh and the Kingdom of Norway (Norway), including mainland Norway, the Svalbard archipelago, and the island of Jan Mayen. The object of this study is to explore the maritime boundary delimitation process followed by Bangladesh and Norway and to find out similarities between both countries in such delimitation. It is qualitative research. In identifying and interpreting data both primary and secondary sources are considered. Primary sources include international treaties, agreements, statutes, case decisions etc. whereas, secondary sources include books, journal articles, and reports of national and international organizations etc. Findings of the study reveal that there is a similarity in the maritime claims of both the countries. Both Bangladesh and Norway claimed straight baselines, 12 nautical mile territorial sea, 24 nautical mile contiguous zone, 200 nautical mile exclusive economic zone and extended continental shelf beyond 200 nautical miles. They have also completed maritime boundary settlement with all the neighbours.